Fundamentals of Data Visualization : A Primer on Making Informative and Compelling Figures - Wilke, Claus O. (USA : O'Reilly Media, 2019)
Effective visualization is the best way to communicate information from the increasingly large and complex datasets in the natural and social sciences. But with the increasing power of visualization software today, scientists, engineers, and business analysts often have to navigate a bewildering array of visualization choices and options.
Keywords: Data Visualization; Fundamentals